Hubungan Body Image dengan Kepercayaan Diri Remaja Putri di Wilayah Rw 024 Kelurahan Tlajung Udik - Mella Ardhya Pramesti; Andi Mayasari Usman; Millya Helen (Universitas Malahayati, 2022)
ABSTRACT Adolescence is a period of transition or transition from children to adults. Adolescence is a process towards maturity and just knowing about wrong and right a problem that has been faced understands his role in socializing, begins to get to know the opposite sex, and knows and accepts his own identity. Physical and emotional changes during adolescence give rise to various views about body image and body image that can affect self-confidence. With the sophistication of body image technology owned by young people, it cannot be separated from their attention through the influences of social media, namely Instagram, Tiktok, YouTube, and other platforms. Purpose to find out the relationship between body image and self-confidence in young women. This study uses a quantitative method with a cross-sectional approach. Sampling using an incidental sampling technique. How to measure using a questionnaire with a measuring instrument using a questionnaire and the data obtained will be analyzed univariate and bivariate using product moment analysis test. The results showed that young women aged 18 to 22 years had a negative body image level of 26.3% while those who had a positive body image level were 73.7%, then 25.6% of young women had low self-confidence. and 74.4% have a high level of confidence. The results of the correlation test using the methods product-moment from Pearson shows that the correlation coefficient (r) is 0.796 and the significance value (p) is 0.000, where the significance (p) is less than 0.05, which indicates that there is a relationship between body image and young women's self-confidence. There is a relationship between body image and self-confidence of adolescent girls. And it is hoped for teenagers to develop their potential. Keywords: Body image, Confidence, Young Women ABSTRAK Masa remaja adalah masa perpindahan atau masa peralihan dari anak- anak menuju dewasa. Remaja merupakan proses menuju usia matang serta baru mengetahui tentang salah dan benar suatu permasalahan yang telah dihadapi, memahami peran dirinya dalam bersosialisasi, mulai mengenal lawan jenis serta mengetahui dan menerima jati dirinya sendiri. Perubahan fisik dan emosional pada masa remaja ini menimbulkan bermacam pandangan mengenai citra tubuh maupun body image yang bisa mempengaruhi kepercayaan diri tersebut. Dengan cangih nya teknologi body image yang dipunyai oleh anak muda tidak lepas dari atensi mereka lewat pengaruh- pengaruh media social ialah instagram, tiktok, youtube dan platform lain nya. Tujuan untuk mengetahui adanya hubungan antara body image dengan kepercayaan diri pada remaja putri. Penelitian ini menggunakan metode kuantitatif dengan pendekatan cros sectioneal. Pengambilan sampel menggunakan Teknik assidental sampling. Cara ukur menggunakan angket dengan alat ukur menggunakan kuisioner dan data yang di peroleh akan di Analisa univariat dan bivariat menggunakan uji analisis produck moment. Hasil penelitian menunjukan bahwa remaja putri berumur 18 sampai 22 tahun memiliki tingkat body image yang negative sebnayk 26,3 % sedangkan yang memiliki tingkat body image positif sebanyak 73,7% , lalu sebanyak 25,6 % remaja putri memiliki tingkat kepercayaan diri yang rendah dan 74,4% memiliki tingkat kepercayaan yang tinggi. Dengan hasil uji korelasi menggunakan metode product moment ini dari pearson bahwa hasil nilai koefisien korelasi ( r ) sebesar 0,796 dan nilai signifikasi (p) 0.000, yang dimana signifikasi (p) lebih kecil dari nilai 0,05 yang menyatakan ada nya hubungan antara body image dengan kepercayaan diri remaja putri. Terdapat hubungan antara body image dan kepercayaan diri remaja putri. Dan di harapkan bagi remaja untuk mengembangkan potensi diri. Kata Kunci : Body image, Kepercayaan diri, Remaja Putri